2011
DOI: 10.1007/s00109-011-0748-0
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase inhibits NF-κB signaling and inflammation: impact on healthspan and lifespan

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a crucial regulator of energy metabolic homeostasis and thus a major survival factor in a variety of metabolic stresses and also in the aging process. Metabolic syndrome is associated with a low-grade, chronic inflammation, primarily in adipose tissue. A low-level of inflammation is also present in the aging process. There are emerging results indicating that AMPK signaling can inhibit the inflammatory responses induced by the nuclear factor-κB (NF-κB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
525
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(556 citation statements)
references
References 117 publications
13
525
1
3
Order By: Relevance
“…Because AMP-activated protein kinase (AMPK) has been reported to have anti-inflammatory and antioxidative stress properties in a variety of cell types, 17,[20][21][22][23][24] we investigated the effects of Fstl1 on the AMPK signaling pathway in mesangial cells. Treatment with FSTL1 protein, at 250 ng/ml, increased the phosphorylation levels of AMPK and its downstream target acetyl-CoA carboxylase (ACC) in human mesangial cells in a time-dependent manner ( Figure 5A).…”
Section: Fstl1 Stimulates Amp-activated Protein Kinase Signaling In Mmentioning
confidence: 99%
“…Because AMP-activated protein kinase (AMPK) has been reported to have anti-inflammatory and antioxidative stress properties in a variety of cell types, 17,[20][21][22][23][24] we investigated the effects of Fstl1 on the AMPK signaling pathway in mesangial cells. Treatment with FSTL1 protein, at 250 ng/ml, increased the phosphorylation levels of AMPK and its downstream target acetyl-CoA carboxylase (ACC) in human mesangial cells in a time-dependent manner ( Figure 5A).…”
Section: Fstl1 Stimulates Amp-activated Protein Kinase Signaling In Mmentioning
confidence: 99%
“…Recently, metformin has also been shown to increase the sensitivity of resistant cells to cisplatin by suppressing STAT3 activity without activation of AMPKa (76). It has been suggested that AMPK suppresses NFkB signaling indirectly via its downstream mediators, such as sirtuin 1, forkhead box protein O (FoxO) family, peroxisome proliferative activated receptor gamma coactivator 1a, and p53; these factors can subsequently repress the expression of inflammatory factors (77). However, whether inhibition of NFkB and STAT3 by metformin in pancreatic cancer cells requires AMPK activation needs further investigation.…”
Section: Nfkb/stat3 Signaling Pathwaymentioning
confidence: 99%
“…An evolutionarily conserved stress response network utilizing AMPK and Forkhead proteins has been described (53,55,57). In yeast, it was shown that the Forkhead protein Hcm1, but not Fkh1 or Fkh2, was phosphorylated by Snf1 under stress conditions (55).…”
Section: Enhanced Stress Resistance Conferred By the Uba Mutation Ismentioning
confidence: 99%